(untitled) (Scientific journal of the Fergana State University, 2026)
The article presents the results of world experience in the field of formation of modern infrastructure, socio-economic development of regions, modernization of the economy, integration of science, education and production based on innovative cooperation of the industry, domestic scientific research, as well as practical approaches to the analysis of the state of manufacturing enterprises. The example of the Basalt Uzbekistan cluster reveals the essence of the formation of an effective innovation system by strengthening innovative thinking, as well as internal and external integration of components (science, education and production) across industries.